Three Decades of Transformation in the East-Central European Countryside - Bański, Jerzy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book identifies, diagnoses and evaluates social and economic processes taking place in the rural areas of Central and Eastern Europe (CEE) states in the last 25 years and affecting the immediate future, with a particular focus on their spatial diversity. It addresses questions related to the rationality of the current development policy and possible results in the future. Contemporary processes of socio-economic development are typified by the fact that spatial and regional disparities are tending to increase. This unfavourable phenomenon manifested both in society and in terms of polarised space needs to be counteracted using an effective development policy. The book highlights issues concerning demography, functional structure and non-agricultural activity, and identifies new challenges arising from membership of the European Union (EU). Accession to the EU and the opportunity to implement support measures has further increased the dynamism of transformation - a process that proceeded under various scenarios and different regulations and assumptions that have yet to be identified and evaluated. Furthermore, the current internal policies of individual CEE states concerning rural areas are diverse and likely to affect differential future development. The book is based on the knowledge and experience of scientists from countries in the region investigated, who have the best understanding of the subject matter and have observed the transformations. It is intended for researchers exploring the development of the countryside and practitioners dealing with regional and national development policies targeting rural areas.
Introduction (Jerzy Bański) -- Part I: Transformation of the Rural Space -- Chapter 1. Spatial Differences of Transformation Processes in the East Central Europe Rural Areas (Jerzy Bański) -- Chapter 2. Agrarian Development in Hungary after the Transition (Bálint Csatári) -- Chapter 3. The Development of Agriculture in Czechia after Colaps of the Eastern Bloc in European context (Jiří Hrabák) -- Chapter 4. Rural-urban Interactions Influences on the Development of the Suburban Rural Areas in Romania (Monica Dumitraşcu) -- Chapter 5. Renewable Energy Development as a Driver of Rural Change: A case of the Czech Republic (Bohumil Frantál) -- Chapter 6. The status and Trends of Human and Territorial Assets in Peripheral Rural Communities of Estonia (Garri Raagmaa) -- Chapter 7. Continuing Peripheralization of Mountain and Border Areas in Bulgaria (Boian Koulov) -- Part II: Demographic and Social Changes -- Chapter 8. Rural Migration Patterns in the Visegrád Group after the Political and Economic Transition - Common Trends and Country-specific Traits (József Lennert) -- Chapter 9. Spatial Differences in Voting Behaviour Among Inhabitants of Rural Areas in Eastern Europe (Mariusz Kowalski) -- Chapter 10. Social and Demographic Development of the Czech Countryside after 1990 (Antonin Vaishar) -- Chapter 11. Position of Rural Areas in Transforming Migration Processes and Patterns in Slovakia (Ladislav Novotný) -- Chapter 12. Changes in the Dynamics and Demographic Structures of the Romanian Rural Population. An Overview of the Post-communist Period (Ines Grigorescu) -- Chapter 13. Functional Changes in Lithuanian Rural Areas: Demographic and Social Consequences (Donatas Bruneika) -- Chapter 14. Territorial Disparities in the Social Development of Rural Areas with Focus on Social Disadvantages Areas (Bianca Mitrică) -- Part III: New Development Challenges and the Future Perspectives -- Chapter 15. East-Central Europe Countryside Future - Three Scenarios (Jerzy Bański) -- Chapter 16. Ambivalent Perception of Globalization Processes in Post-transition Rural Slovakia (Vladimír Székely) -- Chapter 17. Perspectives and Challenges of the Agriculture on the Visegrad Countries Peripheries (Marcin Mazur) -- Chapter 18. Contemporary Transformations and Challenges in the Rural Development of Bulgaria (Veselin Boyadjiev) -- Chapter 19. Behind the Chaotic Micro-level Patterns of Transformation: Land Cover Changes in Hungary (Jenő Zsolt Farkas) -- Chapter 20. Education - Paradigm Shift, Trends in Spatial Differentiation and Importance in Further Development of Polish Rural Areas (Konrad Czapiewski) -- Chapter 21. Current Challenges and the Perspectives for Multifunctional Agriculture in Czechia (Vít Jančák).
Keywords: Human geography; Geography; Human Geography; Regional Geography